Dynamics of Online Relationship Marketing: Relationship Quality and Customer Loyalty in Iranian banks - Garepasha, Akram (2020)
Purpose – The purpose of this paper is to show the dynamics of relationship marketing in e-banking by examining the association between relationship quality and online customer loyalty at different stages of the relationship lifecycle.  Design/methodology/approach – A sample of 651 customers of Iranian banks in East Azerbaijan Province who had used online banking services was selected for the study after completing a questionnaire. The research hypotheses were tested using structural equation modeling and the AMOS23 software.  Findings – The results showed that the level of the customer relationship determines the effect of relationship quality on customer loyalty in e-banking. Specifically, the effect of online commitment on customer loyalty decreases over time. In addition, as the relationship develops between the customer and the business, the influence of online trust on loyalty increases.   Originality/value – The main contribution of this paper is it enriches the relationship marketing literature with respect to the dynamics of relationships by challenging the effectiveness of relationship marketing, especially the use of the same relational constructs (online satisfaction, trust, and commitment) for customers at different stages of the relationship lifecycle.